Macroscopic Fluid Flow Of Low Gradient Magnetophoresis Through Cellulose Matrix - James, Law Kah Chun (Universiti Sains Malaysia, 2022)
In this work, the kinetics of macroscopic fluid flow of iron oxide nanoparticles (IONP) solution through cellulose matrix under low gradient magnetic field (<100